1998
DOI: 10.1074/jbc.273.34.21594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Transcription Regulator with Homology to GC-binding Factor

Abstract: GC-binding factor (GCF) represses transcription of certain genes and is encoded by a 3.0-kilobase mRNA (Kageyama, R., and Pastan, I. (1989) Cell 59, 815-825). The GCF cDNA hybridizes to two additional mRNA species, 4.2 and 1.2 kilobases. We have used differential hybridization to identify a cDNA clone (termed GCF2) for the 4.2-kilobase mRNA and find that it is highly expressed in HUT-102 cells. The open reading frame consists of 2256 nucleotides and encodes a protein of 752 amino acids with a calculated molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…The first, homologous to the ␤3b domain, is a cDNA (U69609 and AJ223075) encoding a transcription factor, GCF2 (32,33). Although transcribed from an independent gene (see mapping data below), this cDNA is ϳ95% identical to exon 1b and parts of the 2 flanking introns of the ␤3 gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first, homologous to the ␤3b domain, is a cDNA (U69609 and AJ223075) encoding a transcription factor, GCF2 (32,33). Although transcribed from an independent gene (see mapping data below), this cDNA is ϳ95% identical to exon 1b and parts of the 2 flanking introns of the ␤3 gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…repressor factor and VDR (53,54). Moreover, recent studies have identified an important mechanism that could up-regulate EGFR expression in human ACF through enhanced Wnt/h-catenin signaling (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…After we obtained a cDNA clone, D40, that binds to GCF, we later discovered that the reported GCF cDNA clone is chimeric, consisting of two different cDNA fragments. One was derived from the GCF2 transcription factor and the other was from unrelated gene product with unknown function (Reed et al, 1998;Takimoto et al, 1999). D40 protein binds to the latter.…”
mentioning
confidence: 99%